Identifikasi Anak Berkebutuhan Khusus (Abk) Pada Sekolah Luar Biasa (Slb) Berdasarkan Buku Saku Berbasis Behavior Checklist - Dahlia, Lilis; Fitriani, Wahidah; Yoselisa, Dani (Batanang : Jurnal Psikologi, 2023)
The purpose of this study is to describe the identification of children with special needs at Special Schools in┬áPadang Panjang Timur District, Padang Panjang City based on behavior checklist-based pocket books. The┬ábackground of this research is that there are still many Special Needs Schools in Padang Panjang Timur District,┬áPadang Panjang City, which do not place students with special needs according to their needs. The researchmethod used is descriptive quantitative research method. The population in this study is Special Schools in┬áPadang Panjang Timur District, Padang Panjang City with a total of 70 students. The sampling technique in thisstudy used a total sampling technique because the number of samples was relatively small, namely 70 samples.┬áThe data was obtained using a scale distribution technique (in the form of a pocket book based on a behaviorchecklist). The data analysis technique in this study was percentage descriptive analysis. The results of this study┬áindicated that there was a discrepancy between the initial identification carried out by the teacher/school and┬áidentification using a behavior checklist-based pocket book. So from this study obtained data on mild mental┬áretardation 44%, moderate mental retardation 13%, identified as autistic 19%, unidentified as autistic 10%,┬áidentified as ADHD 13% and not identified as ADHD as much as 1%.Keywords: Identification, ABK and SLB.